Sodium propionate modulates gut microbiota and blood parameters in healthy mice - Cheng, Wenjie; Zhu, Junhong; Yi, Lanlan; Song, Guangyao; Xie, Yuxiao; Che, Shuailiang; Zhao, Sumei (Frontiers in Microbiology, 2026)
IntroductionShort-chain fatty acids (SCFAs), particularly propionate, play crucial roles in host metabolism, immunity, and gut barrier function. However, the direct physiological effects of propionate on healthy organisms remain unclear. This study investigated the impact of sodium propionate (SP) supplementation on intestinal barrier function, gut microbiota, and hematological parameters in healthy C57BL/6 mice.MethodsMice were orally administered 200 mg/kg SP for 21 days.ResultsResults showed no significant changes in body weight, intestinal histopathology, or blood parameters. The immunohistochemical results showed decreased IL-6 expression, while IL-10 and occludin expression were increased. Gut microbiota analysis revealed decreased α-diversity in the SP group, along with shifts in microbial composition, including increased Akkermansia and Bacteroides. No significant differences in colonic SCFA concentrations were observed.ConclusionThese findings suggest that propionate modulates gut microbiota and hematological parameters in healthy mice, providing insights into its physiological roles under normal conditions.